Effect of age on result of double-layer closure of anterior palatal fistula in BCLP patients - يعقوب , حكمت; شقيره , علي يوسف (Latakia University Journal -Medical Sciences Series, 2022)
Aim: The study of child's age effect on the clinical result of doubled-layer technique closure of anterior palatal fistula in bilateral cleft lip and palate patients. Materials and Methods: (12) Twelve BCLP patients who underwent primary repair and still with a residual anterior palatal fistula attended to oral and maxillofacial department at Tishreen university hospital in Latakia between 2017 and 2020 were included. Their age ranged between 3 and 12 years old with mean age 6,8 years. Each fistula was closed surgically using the premaxillary palatal flap and cover it with the lateral palatal flaps. Results: Four of five fistulas (4/5) of age (3-6 years) and seven of seven fistulas (7/7) of age (7-12 years) were closed completely. By using Chi2 test, no significant differences were found between the two categories. This finding suggests that is no effect of the child's age on the clinical result of anterior palatal fistula closure. Conclusions: This study shows that the child's age has no effect on the result of the doubled-layer technique in anterior palatal fistula closure in bilateral cleft lip and palate patients.